Screening of diabetes mellitus in patients at risk in dermatology outpatient department - Kaul, Kanishka (International Journal of Research in Dermatology, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a widely spread multidisciplinary condition that requires the attention of many different disciplines; yet, the involvement of dermatologists in this regard has not been recognized. The current study focused on the role of dermatologists in screening the prevalence and pattern of cutaneous manifestations in diabetic and pre-diabetic patients. Methods: A randomized study was carried out from April 2023 to October 2023 in the department of dermatology at SSB Heart and Multispecialty Hospital in Faridabad, Haryana. In the current study, patients with dermatological problems suspected of diabetes mellitus were enrolled. Dermatological problems such acanthosis nigricans, dermatophyte infections, psoriasis, endogenous eczema, chronic urticaria, generalized pruritus, lichen simplex chronicus, patients older than 40, and coexisting conditions like obesity were focused in this study. Results: This study enrolled a total of 100 patients. Only 37 patients were recognized as having a high risk of diabetes, with 67.57% having a verified history of the disease. Furthermore, 32% of T2DM patients were examined for specific skin symptoms during their initial visits, with 4 individuals being found to have generalized pruritus and dermatophyte infection. Conclusions: This study finally concluded that dermatologists may play a crucial role in fighting the T2DM epidemic by early detection of T2DM and treatment initiation which may reduce the risk of serious complications.